(3GdYRj aj GdJUQjas - (3GdRfLGfj, YHO GdhgGH Hf EHQGgje Hf YHO GdhgGH, J(B665(3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYdejf GYde Cf GdJUQja aj GddZI GdJZjjQ haj GdUfGYI JMhjd GdCUd GdhGMO Edi CeKdI eNJdaIs
(3BNQgG (B:s
(3bGdhG GUa GLH HGdhGMOI cbhdc QMeJg QMeI hGMOI hGdaYdI HGdcSQI ddfhY Jbhd gh MSf GdWYeI hGdLdSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 179s
(3eYLe GdeDdajf(B: 1 / 42s
(3cTa GdXfhf(B: 2 / 1138s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdUQas